Law Enforcement and Human Rights (The Role of Muhammadiyah in the Humanitarian Case in Kendari) - Muhammad Alifuddin; Suarni Suarni (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
This research aims to describe the role of Muhammadiyah in law enforcement and human rights in Kendari. The main problem that becomes the focus of this study is: what is the role and form of Muhammadiyah involvement in encouraging human rights law enforcement efforts for the 26th September 2019 case in Kendari, and what factors have pushed Muhammadiyah to be involved in this problem? The study of the problem is based on qualitative data obtained through in-depth interviews, observation and document study. The collected data were analyzed using a data analysis mechanism developed by Miles and Hubermen combined with Von Eckartsberg's hermeneutic phenomenological approach. This study concludes: (1). Muhammadiyah as a social element of Islam in Kendari plays a significant role in encouraging the law enforcement process for humanitarian cases that cause the loss of human life. The indicator of this significant role is the success of the Muhammadiyah Advocate Team in bringing and forwarding the related cases to the general court until the Panel of Judges sentenced the defendant to 4 (years) in prison. Second: the form of Muhammadiyah's involvement in cases of law and human rights violations in Kendari is to provide assistance to victims and witnesses and to oversee the law enforcement process down to the court level. Third: the serious efforts shown by Muhammadiyah elements in guarding the process and law enforcement on the 26 September 2019 case cannot be separated from the basic ideology of the Muhammadiyah movement, namely the preaching of amar maruf nahi munkar.